2011
DOI: 10.2478/v10034-011-0019-y
|View full text |Cite
|
Sign up to set email alerts
|

Turner Syndrome with Isochromosome Xq and Familial Reciprocal Translocation t(4;16)(p15.2;p13.1)

Abstract: We present here a 16-year-old Turner syndrome patient with a complex karyotype that includes a maternally-inherited balanced translocation between chromosomes 4 and 16 and mosaicism of the isochromosome Xq10. Her karyotype was 45,X,t(4;16) (p15.2;p13.1)[9]/46,X,i(X) (q10),t(4;16)(p15.2;p13.1) [91]. The karyotype of her father was normal, whereas that of her mother had the same balanced translocation and numerical abnormalities of chromosome X and was designated as 45,X,t(4;16)(p15.2;p13.1) [2]/46,XX,t(4;16)(p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…In a family case, mother and daughter have X chromosome abnormalities and a balanced translocation with a 45,X,t ( [11]. This highlighted the relevance of parental chromosome analysis of TS patients with a reciprocal, not only to identify the origin of the but also to evaluate whether parents carry numerical X chromosome abnormalities in a mosaic form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a family case, mother and daughter have X chromosome abnormalities and a balanced translocation with a 45,X,t ( [11]. This highlighted the relevance of parental chromosome analysis of TS patients with a reciprocal, not only to identify the origin of the but also to evaluate whether parents carry numerical X chromosome abnormalities in a mosaic form.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of autosomal translocations and structural/numerical abnormalities of the X chromosome are a rarely reported, there are 12 cases published [9][10][11][12][13][14][15][16][17][18][19][20]. Here we describe a mosaic Turner syndrome patient with a maternally inherited reciprocal translocation with breakpoints at 2p13 and 12q24.…”
Section: Open Accessmentioning
confidence: 99%
“…In a cohort of 146 Serbian patients with Turner syndrome, a 12-year old girl with short stature, primary amenorrhea with autosomal translocation of chromosomes 12 and 14, that is, 45X/46XX, t(12,14), was found [15]. Cetin et al reported an inherited reciprocal translocation and structural abnormality of the X chromosome (isochromosome Xq) in 16-year-old patient with Turner somatic features [16]. Our patient did not present at that time evident Turnerian phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…5 Además, la duplicación de una región en el cromosoma 17p13.3 ha emergido como un nuevo síndrome distintivo (OMIM #613215). 9 L a s c a r a c t e r í s t i c a s f e n o t í p i c a s d e e s t e síndrome incluyen restricción del crecimiento intrauterino (RCIU), retardo del desarrollo psicomotor, hipotonía, dismorfismo craneofacial, braquidactilia, falanges distales acortadas, hallux valgus, de leve a moderado déficit cognitivo, problemas comportamentales pertenecientes a l e s p e c t r o a u t i s t a y , o c a s i o n a l m e n t e , malformaciones cerebrales que afectan el cuerpo calloso, el cerebelo y la fosa posterior.…”
Section: Figura 3 Cariotipo De La Pacienteunclassified
“…1,4 El cariotipo en aproximadamente el 50% de las pacientes con síndrome de Turner muestra una monosomía X universal (45,X), seguida en frecuencia por isocromosomas del brazo largo del cromosoma X de forma universal [46,X,i(X) (q10)] y finalmente por los mosaicismos de la monosomía X y el isocromosoma Xq [i(Xq)]. 5,6 La asociación del síndrome de Turner con rearreglos en el cromosoma 17 y una forma de catarata congénita con herencia autosómica dominante (AD) y penetrancia incompleta no ha sido descrita previamente, ya que incluso esta forma de catarata de forma aislada es excepcionalmente rara.…”
Section: Introductionunclassified